Procampylaspis spinifera Petrescu 2006, sp. nov. ... - Petrescu, Iorgu (Zenodo, 2006)
Procampylaspis spinifera sp. nov. Figures 47–50 Material examined. Holotype female, Tas., off Freycinet Peninsula, 42°00.20'S, 148°37.70'E, 720 m, coarse shelly sand, WHOI epibenthic sled, M.F. Gomon et al., RV Franklin, 27 Jul 1986 (stn SLOPE 46), NMV J53003. Allotype male: (stn SLOPE 45), NMV J53004. Paratypes: 2 immature males (stn SLOPE 46), NMV J53006; 1 female, dissected (stn SLOPE 45), NMV J53007; 1 male, dissected (stn SLOPE 46), NMV J53008; 1 female (stn SLOPE 46), MGAB CUM 1619. Diagnosis. Carapace with 5 pairs of dorsal spines, pair of spines on top of ocular lobe, anterolateral margin with strong serration. Pair of dorsal spines on pereonites 3–5 and pleonite 1. Strongly serrated basal article of antenna 1 peduncle. Maxilliped 2 with 5 dactylar teeth, 1st one as long as 3rd, 5th tooth twice as long as 3rd tooth. Maxilliped 3 with strong tooth on outer margin of merus. Pereopod 1 with merus longer than carpus but shorter than propodus. Pereopod 2 with spine on inner margin of merus, dactylus 2.8 ... : Published as part of Petrescu, Iorgu, 2006, Nannastacidae (Crustacea: Cumacea) from eastern Bass Strait, the south-eastern Australian slope, and Antarctica in the collections of Museum Victoria, pp. 129-173 in Memoirs of Museum Victoria 63 (2) on pages 159-161, DOI: 10.24199/j.mmv.2006.63.14, http://zenodo.org/record/10665606 ...